Overcoming the Stromal Barrier of the Cornea with a Peptide Conjugate Nano‐Assembly to Combat Fungal Keratitis (Adv. Healthcare Mater. 10/2023). Issue 10 (17th April 2023) - Ju, Xiaoyan; Wu, Liping; Gao, Ning; Tian, Ye; Lu, Guojun; Gao, Yichen; Zhao, Shaozhen; Niu, Zhongwei; Yang, Ruibo
Abstract : Fungal Keratitis In article 2202409, Shaozhen Zhao, Zhongwei Niu, Ruibo Yang, and co‐workers report a peptide conjugate nano‐assembly (PCNA) that permeates corneal stroma and kills the hyphae without irritating the ocular cornea. PCNA with a nano‐assembled structure and assembly–disassembly behavior could serve as the foundation of a new therapy for fungal keratitis.